With the given information we can deduce:
[tex]\dfrac{f(3)-f(0)}{3} = -1 \implies f(3)-f(0)=-3[/tex]
[tex]\dfrac{f(3)-f(2)}{1} = 5 \implies f(3)-f(2)=5[/tex]
[tex]\dfrac{f(6)-f(2)}{4} = 3 \implies f(6)-f(2)=12[/tex]
The average rate of change over [0,6] would be
[tex]\dfrac{f(6)-f(0)}{6}[/tex]
We can add and subtract the same quantities in order to rewrite this quantity in terms of known quantities:
[tex]\dfrac{f(6)-f(0)}{6} = \dfrac{(f(6)-f(2))-(f(3)-f(2))+(f(3)-f(0))}{6} = \dfrac{12-5-3}{6}=\dfrac{4}{6}=\dfrac{2}{3}[/tex]